When Should We Worry about Inflation? - Espinoza, Raphael; Leon, Hyginus; Prasad, Ananthakrishnan (Oxford University Press on behalf of the World Bank, 2013)
At what level should inflation be a concern? From a growth perspective, high and rising levels of inflation as in 2006–2008 raise concerns that inflation, if uncontained, could undermine growth. On the other hand, higher levels of inflation could create more space for using monetary policy to reduce nominal and real interest rates during financial crises. A nonlinear growth regression for 165 countries over 1960–2007 shows that for developing countries, inflation above 10 percent quickly hurts growth. For advanced economies, there is no specific threshold: in the medium term, higher inflation hurts growth for any initial level of inflation, suggesting that there is a real cost to maintaining higher inflation as a buffer.